2016
DOI: 10.1016/j.ajp.2015.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular diseases among patients with schizophrenia

Abstract: The presence of comorbid physical illnesses especially, cardiovascular diseases (CVD) in schizophrenia is a growing area of concern in recent years. In order to reduce disease burden, to improve quality of life and to provide holistic care, it is important to know

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 75 publications
1
35
0
8
Order By: Relevance
“…A Danish study [18] investigating the association between exposure to cardioprotective treatment after myocardial infarction and mortality rates, found that treatment decreased the mortality hazard rate (HR) ratio in patients diagnosed with schizophrenia from 8.87 to 1.97, and in the general population, lack of treatment increased the HR to 2.95 from 1 (reference value). At baseline, we found patients with schizophrenia to have almost double the prevalence of diabetes, COPD, and stroke, which corresponds to the values found in previous research [2,[18][19][20][21]. Over time, risk factors for ischemic heart disease, including diabetes mellitus, hypertension, and COPD, were also increasingly prevalent.…”
Section: Time Trends In Guideline-based Therapysupporting
confidence: 88%
See 1 more Smart Citation
“…A Danish study [18] investigating the association between exposure to cardioprotective treatment after myocardial infarction and mortality rates, found that treatment decreased the mortality hazard rate (HR) ratio in patients diagnosed with schizophrenia from 8.87 to 1.97, and in the general population, lack of treatment increased the HR to 2.95 from 1 (reference value). At baseline, we found patients with schizophrenia to have almost double the prevalence of diabetes, COPD, and stroke, which corresponds to the values found in previous research [2,[18][19][20][21]. Over time, risk factors for ischemic heart disease, including diabetes mellitus, hypertension, and COPD, were also increasingly prevalent.…”
Section: Time Trends In Guideline-based Therapysupporting
confidence: 88%
“…Schizophrenia is associated with higher mortality rates than those in the general population mainly driven by natural causes of death, including acute coronary syn-drome (ACS) [1][2][3][4]. Hypotheses regarding the causal factors resulting in the increased mortality are many, nonetheless data support an increased prevalence of cardiac risk factors, metabolic side effects following the use of antipsychotic medication, as well as a decreased awareness or ability to describe symptoms in patients and a potential bias towards the patient from professionals [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…These nutrients are beneficial for mental health. Conversely, excess intake of saturated fat and sugar, which are risk factors for CVD, is detrimental to brain function 11 .…”
Section: Nutritional Factors Affecting Mental Healthmentioning
confidence: 99%
“…Insulin resistance is a major factor in the development of diabetes mellitus (Tang, Li, Song, & Xu, 2015), and inflammation plays a role in the pathogenesis of cardiovascular disease (Kanda & Takahashi, 2004;Ridker, Hennekens, Buring, & Rifai, 2000). These processes are highly relevant to schizophrenia, as this population has a high rate of obesity and cardiovascular disease (Azad et al, 2016;Ringen, Engh, Birkenaes, Dieset, & Andreassen, 2014;Ward & Druss, 2015), leading to increased morbidity and mortality relative to the general population. Although relationships have been discovered between PPFs, health variables, and blood-based biomarkers in other populations (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…physical comorbidity, cardiovascular disease risk). We examined biomarkers of insulin resistance and inflammation due to their relevance to the health of persons with schizophrenia (Azad et al, 2016;Ringen et al, 2014;Ward & Druss, 2015), and because these two types of biomarkers have been found to be associated with positive psychological well-being and positive affect in other populations (Osama & Shehab Ael, 2015;Phillips & Perry, 2015;Steptoe et al, 2012;Steptoe et al, 2008). We hypothesized that the schizophrenia group would have lower mean levels of resilience, optimism, and happiness, and higher levels of perceived stress, relative to the HC group.…”
Section: Introductionmentioning
confidence: 99%